Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 6 - Algebra: Equations and Inequalities - 6.2 Linear Equations in One Variable and Proportions - Exercise Set 6.2: 31

Answer

{-4}

Work Step by Step

8y - 3 = 11y + 9 Step 1 : Collect variable terms on one side and constants on the other side. subtract 11 y from both the sides 8y - 3 - 11y= 11y + 9 - 11y Simplify -3 y -3 = 9 Add 3 on both the sides -3y -3 + 3 = 9 +3 Simplify -3y = 12 Divide both the sides by -3 $\frac{-3y}{-3}$ = $\frac{12}{-3}$ x =-4 Now we check the proposed solution, -4 , by replacing y with -4 in the original equation. Step 1: the original equation 8y - 3 = 11y + 9 Step2: Substitute -4 for y 8(-4)- 3 = 11 (-4) + 9 Step 3: Multiply 8.(-4) = -32, 11(-4) = -44 -32 - 3 = -44 + 9 Step 4: Solve -35 = -35 Since the check results in true statement, we conclude that the solution set of the given equation is {-4}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.